The International Ticer School: Getting Inspired to Shape your Library of the Future - Prinsen, Jola G.B. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Tilburg University in the Netherlands was the first university in Europe to develop a strategic vision of the digital library (Wieërs, 1989 and 1990). This strategy focussed on electronic access to information from the users’ desktops. In 1992, the library managed initially to implement these ideas with a new library building, 450 desktop computers for students in the library, and integrated access to various electronic information sources for all university staff and students (Dijkstra, 1994; Geleijnse & Roes, 1996).